[Für die kunstliebenden und vaterländische Jugend von der Musik-Gesellschaft auf der teutschen Schule in Zürich] 1773-76; 1779-80 (Zürich Deutsche Schule, 1773)
In the 17th century music in Zürich was dominated by three collegia musica: the first was ‘zum Chorherrensaal’, followed by the ‘ab dem Musiksaal’ (from 1613) and ‘zur deutschen Schule’ (from 1679). Initially they were concerned only with sacred music, but later also performed contemporary German and Italian secular music. The three societies merged in 1812 to form the Allgemeine Musikgesellschaft Zürich (AMGZ), which since 1813 has produced books on musical subjects in a series of ‘Neujahrsblättern’, the successors to a series of New Year collections of polyphonic pieces published by two of the collegia musica from 1685 and 1713 respectively.
Die Ankündigung der Seligkeit für die Friedfertigen Vorgestellet nach Matth. Cap.V v.9. und der kunstliebenden Jugend verehrt von der Vereinigten Music-Gesellschaft in der Grösseren Stadt auf der Teutschen Schul in Zürich - Die Ankündigung der Seligkeit für die; welche um Christi und um der Gerechtigkeit willen geschmähet und verfolget werden. Vorgestellet nach Matth. Cap.V. v.10, 11, 12. Von der Lobl. Vereingten Music-Gesellschaft in der Grösseren Stadt auf der Teutschen Schul in Zürich - Der Frühling der Natur, Ein anmutiges und treffendes Bild der frohen Auferstehung und des immerwährenden Frühlings des ewigen Lebens. Der kunstliebenden Jugend verehrt von der Vereinigten Music-Gesellschaft in der Grösseren Stadt auf der Teutschen Schul in Zürich - Die Betrachtung des Winters als eine Ermunterung zur Erwegung Allmacht Gottes. Der kunstliebenden Jugend verehrt von der Vereinigten Music-Gesellschaft in der Grösseren Stadt auf der Teutschen Schul in Zürich - Neujahrsgeschenk für die vaterländische Jugend von der Musik-Gesellschaft auf der teutschen Schule in Zürich
Collection of fragments of a larger unknown publication (paginated 483-538, with plates nr LXI, LXII, LXIV, LXVII) and another section in different page dimensions and folded pages.
See 04J21, 10B20, 11H13, 26D03, G1-027 and G1-028 for similar collections
Contains 4 beautiful engravings by Johann Rudolf Holzhalb (1723-1806)
Originally published in 1754
Keywords: Allgemeine Musikgesellschaft Zürich (Switzerland); 18th Century (1701-1800); Vocal music; Education; Religion; Poetry; Moral education; Song; Emblem; Zürich (Switzerland)